Postnatal High-Fat Diet Increases Liver Steatosis and Apoptosis Threatened by Prenatal Dexamethasone through the Oxidative Effect - Huang, Ying-Hsien (Int J Mol Sci, 2016)
The objective of this study was to investigate cellular apoptosis in prenatal glucocorticoid overexposure and a postnatal high fat diet in rats. Pregnant Sprague-Dawley rats at gestational days 14 to 21 were administered saline (vehicle) or dexamethasone and weaned onto either a normal fat diet or a high fat diet for 180 days; in total four experimental groups were designated, i.e., vehicle treated group (VEH), dexamethasone treated group (DEX), vehicle treated plus high-fat diet (VHF), and dexamethasone treated plus high-fat diet (DHF). Chronic effects of prenatal liver programming were assessed at postnatal day 180. The apoptotic pathways involved proteins were analyzed by Western blotting for their expressions. Apoptosis and liver steatosis were also examined by histology. We found that liver steatosis and apoptosis were increased in the DHF, DEX, and VHF treated groups, and that the DHF treated group was increased at higher levels than the DEX and VHF treated groups. The expression of leptin was decreased more in the DHF treated group than in the DEX and VHF treated groups. Decreased peroxisome proliferator-activated receptor-gamma coactivator 1α, phosphoinositide-3-kinase, manganese superoxide dismutase and increased malondialdehyde expression levels were seen in DHF treated group relative to the DEX treated group. The DHF treated group exhibited higher levels of oxidative stress, apoptosis and liver steatosis than the DEX treated group. These results indicate that the environment of high-fat diet plays an important role in the development of liver injury after prenatal stress.